Hyaloscypha gabretae and Hyaloscypha gryndleri spp. nov. (Hyaloscyphaceae, Helotiales), two new mycobionts colonizing conifer, ericaceous and orchid roots - Vohník, Martin; Figura, Tomáš; Réblová, Martina (Mycorrhiza, 2022)
Historically, Hyaloscypha s. lat. (Hyaloscyphaceae, Helotiales) included various saprobes with small apothecia formed on decaying plant matter, usually wood, that were defined by chemical and (ultra)structural aspects. However, recent molecular phylogenetic and resynthesis studies have narrowed the concept of the genus and shown that it contains several widely distributed species with unknown sexual morphs that form ectomycorrhizae, ericoid mycorrhizae, and mycothalli and also grow endophytically in plant roots and hypogeous ectomycorrhizal (EcM) fruitbodies (i.e., the historical Hymenoscyphus ericae aggregate). Hence, some of the sexually reproducing saprobic Hyaloscypha s. lat. and the symbionts belong to the monophyletic Hyaloscypha s. str. Here, we introduce two new root-symbiotic Hyaloscypha s. str. species, i.e., H. gabretae and H. gryndleri spp. nov. While the former was isolated only from ericaceous hosts (Vaccinium myrtillus from Southern Bohemia, Czechia and Calluna vulgaris from England, UK), the latter was obtained from a basidiomycetous EcM root tip of Picea abies (Pinaceae), roots of Pseudorchis albida (Orchidaceae), and hair roots of V. myrtillus from Southern Bohemia and C. vulgaris from England. Hyaloscypha gryndleri comprises two closely related lineages, suggesting ongoing speciation, possibly connected with the root-symbiotic life-style. Fungal isolates from ericaceous roots with sequences similar to H. gabretae and H. gryndleri have been obtained in Japan and in Canada and Norway, respectively, suggesting a wide and scattered distribution across the Northern Hemisphere. In a series of in vitro experiments, both new species failed to form orchid mycorrhizal structures in roots of P. albida and H. gryndleri repeatedly formed what morphologically corresponds to the ericoid mycorrhizal (ErM) symbiosis in hair roots of V. myrtillus, whereas the ErM potential of H. gabretae remained unresolved. Our results highlight the symbiotic plasticity of root-associated hyaloscyphoid mycobionts as well as our limited knowledge of their diversity and distribution, warranting further ecophysiological and taxonomic research of these important and widespread fungi.
Keywords: Mycorrhizae; Ericoid mycorrhizal fungi; kořeny rostlin; Phylogeny; Plant Roots; Ascomycota; Pezoloma ericae; Rhizoscyphus ericae; Meliniomyces; mykorhiza; Hymenoscyphus ericae; Hyaloscypha hepaticicola; Root symbiotic fungi; fylogeneze; Tracheophyta; Core Ericaceae; cévnaté rostliny